EVALUATION OF THE PREPARATION AT STANDARD OPERATING PROCEDURES FOR GOVERNMENT ADMINISTRATION - Zahid Husain Al Faruqi; Izzatusholekha Izzatusholekha; Rahmat Salam; Muhammad Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Population and Civil Registration Service of the South Tangerang City Government is a public service provider that has the widest range of services and is very susceptible to distortion, so it requires very effective and efficient service procedures. The aim of this research is to determine the results of the evaluation analysis of the process of preparing standard operational procedures for government administration in services at the Population and Civil Registration Service of the South Tangerang City Government. The theory used in this research is William N Dunn's evaluation theory with six evaluation dimensions, namely effectiveness, efficiency, equity, adequacy, responsiveness and accuracy. The research method used is a descriptive research method with a qualitative approach. The data collection techniques used are interviews, observation and documentation, while the data analysis techniques used are data reduction, data presentation and drawing conclusions. The informant is an internal employee of the Population and Civil Registration Service of the South Tangerang City Government. The results of this research illustrate that the limited workload of employees to carry out activities is the root of the complexity of problems which results in a decrease in employee understanding of regulations, inefficient use of budgets, obstacles in implementing activities that cannot be properly mitigated to the level of document relevance, but the implementation of orderly service delivery. based on monitoring complaints and increasing perceptions of public satisfaction with service procedures, changing the view of various problems that arise so that the researcher concludes that the AP SOP document which is prepared bottom up does not significantly influence the activity implementation process because the activity implementer does not refer to the AP SOP document in text. book in carrying out tasks.